Bone density, microarchitecture and strength in elite figure skaters is discipline dependent - Burt, L. A.; Groves, E. M.; Quipp, K.; Boyd, S. K. (Journal of Science and Medicine in Sport, 2022)
Objectives: In elite figure skaters, to determine if there was a difference in volumetric bone mineral density and bone strength between 1) figure skaters and population-based normative data, 2) single or pair skaters and ice dancers, and 3) the landing and takeoff legs. Design: Cross-sectional. Methods: Figure skaters had their non-dominant distal radius and bilateral tibia scanned using high-resolution peripheral quantitative computed tomography. Volumetric bone mineral density was determined at the total, cortical and trabecular compartments, and finite element analysis estimated bone strength. Normative data was used to compare the total bone mineral density of figure skaters to a population-based cohort. Independent t-tests compared differences between skating discipline, and paired t-tests compared skeletal parameters for the landing and takeoff leg. Results: Twenty elite skaters (mean age 22±6.2; female=11, male=9) completed scans. Compared with the general population, the mean percentile rank for skaters' total volumetric bone mineral density was below normal at the radius (27th percentile) and normal at the tibia (54th percentile). Single or pair skaters had more robust bone in the landing compared with their takeoff leg. Specifically, the landing leg had higher total bone mineral density (2.8%) and trabecular bone mineral density (6.5%), and superior bone strength (8.5%) than the takeoff leg (p<0.05). Conclusions: Volumetric bone mineral density and strength differences in figure skaters were discipline dependent. Side-to-side differences were observed in single and pair skaters where the landing leg is denser, larger and stronger than the takeoff leg.